Islamic Banks - Ismail, Naima; Sabri bin Haron, Mohamad (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Islamic banks has development in many aspects in practical performance of banks function, this was a limited activity in service Banks and commercial processes. Later, it came to They possess financial power and ability to create Islamic loans. They possess financial power and ability to create Islamic loans. Economical union supported by banks is not restricted to a domestic sphere, but has expanded internationally as its operations enjoy fidelity and fulfillment between banking organizations in different countries. As banking systems Islamic banks had developed, they are no longer restricted to role of being financial and service organizations, but have become money market within public sector. Furthermore, they follow up monetary flows and banking securities, by playing positive role of providing the organized money market with enough information about commercial activities. In addition, as a financial mediator who has adequate statistics about other economical units, besides its main role in creating successful development plans and riskless investment.